Evaluating demand responsive transit services using a density-based trip rate metric - Kaufman, Benjamin; Leung, Abraham; Burke, Matthew (Journal of Transport and Land Use, 2021)
Demand responsive transit (DRT) is attracting increased attention as a means to provide public transit to low-density populations. This research aims to provide a suite of evaluation metrics with low data requirement and widespread availability, so that operators, funders, regulators, and practitioners can better evaluate the performance of DRT services. Trip numbers can be divided by a number of available variables (period, trip length, population, and density) to create a number of derived metrics. By applying these variables across three different DRT service areas in Logan City, Australia, where other key factors are held constant, one can see how different formulations lead to very different readings of DRT system performance. The results confirm the dilemma of cost efficiency versus equity in service provision in low-density environments. This paper also highlights current data limitations and calls for better data collection to facilitate the development of new evaluation methods for DRT services and a new composite metric that can be used for inter-service comparison.